AZAN DALAM MELEPAS PENGANTIN PEREMPUAN DIKALANGAN MASYARAKAT KEC. HURISTAK KAB. PADANG LAWAS - Risalan Basri Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This paper is an attempt to find out people's perceptions of the call to prayer in the departure of the bride in the Huristak district of Padang. The question that the author wants to answer is how is the public perception of the call to prayer in the departure of the bride in the community of Huristak district. What is the reason for the call to prayer in the departure of the bride in the Huristak district of Padang Padang.From the author's analysis, it can be concluded that the call to prayer in the departure of the bride in the community of the Huristak district of Padang Padang is aimed at informing the general public that the bride and groom will be dispatched to the groom's house, in accordance with the function of the call to prayer in the prayer namely to call on the people, then in the departure of the bride too, too.The community's reason for announcing the call to prayer in the departure of the bride is that it is not the texts that govern it both in the Qur'an and the hadiths but rather only the tradition that develops in the community because the function of the call to prayer is to cry out in the implementation